2016
DOI: 10.1007/s12016-015-8526-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Immunobiology of Eosinophils in the Respiratory System: a Comprehensive Review

Abstract: The eosinophil is a fully delineated granulocyte that disseminates throughout the bloodstream to end-organs after complete maturation in the bone marrow. While the presence of eosinophils is not uncommon even in healthy individuals, these granulocytes play a central role in inflammation and allergic processes. Normally appearing in smaller numbers, higher levels of eosinophils in the peripheral blood or certain tissues typically signal a pathologic process. Eosinophils confer a beneficial effect on the host by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 149 publications
0
27
0
1
Order By: Relevance
“…While the presence of eosinophils is not uncommon even in healthy individuals, these granulocytes play a central role in the pathogenesis of allergic inflammation, particularly in the respiratory system, such as asthma 19. Results of our study showed that after sensitization and challenge with OVA, the number of total inflammatory cells, eosinophils, macrophages and lymphocytes increased significantly in BALF.…”
Section: Discussionmentioning
confidence: 50%
“…While the presence of eosinophils is not uncommon even in healthy individuals, these granulocytes play a central role in the pathogenesis of allergic inflammation, particularly in the respiratory system, such as asthma 19. Results of our study showed that after sensitization and challenge with OVA, the number of total inflammatory cells, eosinophils, macrophages and lymphocytes increased significantly in BALF.…”
Section: Discussionmentioning
confidence: 50%
“…First, since the peripheral blood sample of a patient with bronchial asthma often shows eosinophilia (4), we did not consider eosinophilia as a sign of eosinophilic myocarditis. It is important to suspect eosinophilic myocarditis in patients with chest pain and eosinophilia, even if they have other diseases that are associated with eosinophilia, such as bronchial asthma, collagen disease, or hematological disorders (5).…”
Section: Discussionmentioning
confidence: 99%
“…In eosinophilic asthma, also described as T H 2 asthma, the rise in the number of eosinophils in the airways starts when the airway epithelium is exposed to an allergen or antigen, thus causing the activation of an immunological cascade that drives eosinophils to the airways by T H 2 cytokines and chemoattractants [87]. When helper T cells are activated by an allergen, they skew to the T H 2 phenotype and start to secrete IL-4, IL-5, and IL-13 [88,89]. IL-5 and RANTES have been reported to be the most potent inducers of eosinophil migration into the asthmatic lung [90].…”
Section: Eosinophil Recruitment and Survival: Key Steps In The Pathopmentioning
confidence: 99%
“…In acute idiopathic eosinophilic pneumonia, eosinophils accumulate and damage the airways by means of a currently unclear mechanism that may be related to clonal T cells [128]. Chronic eosinophilic pneumonia has also been described, although compared with the acute disorder, the chronic form is often associated with previous asthma or atopy [88,129]. Pulmonary fibrosis is also caused by the accumulation of eosinophils, although in this case it is accompanied by neutrophils, and its pathophysiology is caused by interstitial collagen deposition, which leads to fibrosis [88,130].…”
Section: Eosinophilic Disordersmentioning
confidence: 99%